2016
DOI: 10.3389/fmicb.2016.01820
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Mathematical Modeling to Understanding Dynamic Aspects of Rumen Metabolism

Abstract: All mechanistic rumen models cover the main drivers of variation in rumen function, which are feed intake, the differences between feedstuffs and feeds in their intrinsic rumen degradation characteristics, and fractional outflow rate of fluid and particulate matter. Dynamic modeling approaches are best suited to the prediction of more nuanced responses in rumen metabolism, and represent the dynamics of the interactions between substrates and micro-organisms and inter-microbial interactions. The concepts of dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 86 publications
(171 reference statements)
0
38
0
3
Order By: Relevance
“…A more recent meta-analysis by White et al (2016) compared empirical and mechanistic (i.e., microbial N as a function of ruminal carbohydrate digestibility) approaches to predict MPS and concluded that predicting MPS empirically had the lowest prediction error. In a review by Bannink et al (2016), it was delineated what added value mechanistic approaches may have above empirical approaches by representing the interactions between various rumen pools (substrate, microbial, and metabolites) to explain the more dynamic aspects of rumen fermentation, which an empirical approach cannot give. The latter approaches normally adopt the concept of additivity of predicted MPS values for the individual dietary components and are, in essence, linear models not accounting for nonlinear effects.…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 99%
“…A more recent meta-analysis by White et al (2016) compared empirical and mechanistic (i.e., microbial N as a function of ruminal carbohydrate digestibility) approaches to predict MPS and concluded that predicting MPS empirically had the lowest prediction error. In a review by Bannink et al (2016), it was delineated what added value mechanistic approaches may have above empirical approaches by representing the interactions between various rumen pools (substrate, microbial, and metabolites) to explain the more dynamic aspects of rumen fermentation, which an empirical approach cannot give. The latter approaches normally adopt the concept of additivity of predicted MPS values for the individual dietary components and are, in essence, linear models not accounting for nonlinear effects.…”
Section: Invasive or Direct Methods For Assessing Feed Protein Degradmentioning
confidence: 99%
“…The present model takes into account interactions between different types of nutrients and the interaction with microbial activity. Therefore, its use may significantly improve the prediction of feed digestion in comparison to current static feed evaluation systems (Bannink et al, 2016). This feature is clearly illustrated by the prediction of a reduced digestion of rumen digestible fiber on diets that contain a large fraction of concentrate feeds (Figure 3).…”
Section: The Added Value Of the Followed Approachmentioning
confidence: 99%
“…However, 103 L/day, the turnover of ruminal fluid, was considerably lower than the PRV observed in our present investigation in the range of 579–1,146 L/day of 538–783‐kg cows (average = 628 kg) (Table ). Although some studies indicated that the ruminal liquid turnover varied from 2.8 to 4.5 (Bannink, van Lingen, Ellis, France, & Dijkstra, ; Gregorini, Beukes, Waghorn, Pacheco, & Hanigan, ; Holden, Muller, Varga, & Hillard, ), the PRV was still high even considering the rumen volumes (RV) estimated based on these studies. On the other hand, SCFAs yield (mol/day) ( Y ) estimated by using the PRV in this study was highly related to it ( X ) estimated by a formula: total SCFAs production (mol/day) = 4.7 × DMI (kg) (Noziere et al., ).…”
Section: Resultsmentioning
confidence: 99%